A microfoundations approach to transnational capabilities: The role of knowledge search in an ever-changing world - Morris, Shad; Hammond, Ryan; Snell, Scott (Journal of International Business Studies, 2014)
Scholars seeking to understand the origin of dynamic capabilities have struggled to articulate specific capabilities and locate their source of variation within the firm. We propose that the transnational imperative and a microfoundations approach to knowledge search can help to develop this topic. Adopting an engaged scholarship approach, hypotheses are tested in a global consulting company. Counter to traditional capabilities arguments, we find that drawing from globally dispersed colleagues will more strongly impact local responsiveness than drawing from locals outside the company – though both may still be needed. Efficiency increases when teams draw upon codified knowledge but decreases when they draw upon embedded tacit knowledge. Finally, through continual learning teams can change and re-direct the composition of their responsiveness and efficiency activities in ways sensitive to an ever-changing world.